2006
DOI: 10.1063/1.2337083
|View full text |Cite
|
Sign up to set email alerts
|

Uncooled infrared imaging using bimaterial microcantilever arrays

Abstract: We report on fabrication and characterization of arrays of bimaterial microcantilevers and discuss their performance as uncooled infrared imagers. An optical readout was used to simultaneously measure deflections of all microcantilevers in the array. The fabricated arrays had an average noise equivalent temperature difference (NETD) and a response time of 1.5K and 6ms, respectively. Some microcantilevers in the array exhibited NETD values below 500mK, approaching our theoretical prediction of 151mK. A unique a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
41
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(44 citation statements)
references
References 8 publications
2
41
0
1
Order By: Relevance
“…In 2006, Grbovic et al of the Oak Ridge National Laboratory (Ten− nessee) reported a high resolution 256×256 pixel array [70]. The fabricated arrays had NEDT and response time of below 500 mK and 6 ms, respectively.…”
Section: Novel Uncooled Infrared Detectorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2006, Grbovic et al of the Oak Ridge National Laboratory (Ten− nessee) reported a high resolution 256×256 pixel array [70]. The fabricated arrays had NEDT and response time of below 500 mK and 6 ms, respectively.…”
Section: Novel Uncooled Infrared Detectorsmentioning
confidence: 99%
“…The high sensitivity of the cantilevers allows the individual pixels in the array to be shrunk from their current size of 50 μm to 20 μm while maintaining low−distortion IR imaging [25,40]. Considerable progress to reduce NEDT and time con− stant has been made in years by several research groups [20,25,[30][31][32][33]40,50,60,61,70,71]. Multispectral Imaging Inc. has developed a new class of electrically−coupled transdu− cers in which bending of the cantilever causes changing its capacitance.…”
Section: Novel Uncooled Focal Plane Arraysmentioning
confidence: 99%
“…[70][71][72] or "A new approach to IR bimaterial detectors theory" by Djurić, et al [77]. A milestone in ORNL activities has been reached with the presentation of real room−temperature thermal images ob− tained with a bi−material cantilever FPA with a "quasi" 4f optical readout in 2006 [78,79]. The presented FPA con− sisted of a 75 μm pitch 256×256 pixel.…”
Section: Oak Ridge National Laboratorymentioning
confidence: 99%
“…SiN x has a thermal conductivity value between those of single-crystal Si and SiO 2 . Typically, suspended SiN x beams with less than 1 μm × 1 μm cross section and 20 to 50 μm length provide the thermal isolation sufficient for high-performance thermal imaging [2,7]. Optimizing the thermal isolation in uncooled IR detectors involves a challenging trade-off between low thermal conductivity and high stiffness.…”
mentioning
confidence: 99%
“…Focal plane arrays (FPAs) of such devices with optical [1][2][3][4][5][6][7] and capacitive [8] readouts were used as uncooled IR imagers in a series of recent efforts. Fabrication of micromechanical IR detectors is scalable to multimegapixel arrays [9].…”
mentioning
confidence: 99%